Translational Windows in Chordoma: A Target Appraisal - Hoffman, Samantha E.; Al Abdulmohsen, Sally A.; Gupta, Saksham; Hauser, Blake M.; Meredith, David M.; Dunn, Ian F.; Bi, Wenya Linda (Frontiers in Neurology, 2020)
Chordomas are rare tumors that are notoriously refractory to chemotherapy and radiotherapy when radical surgical resection is not achieved or upon recurrence after maximally aggressive treatment. The study of chordomas has been complicated by small patient cohorts and few available model systems due to the rarity of these tumors. Emerging next-generation sequencing technologies have broadened understanding of this disease by implicating novel pathways for possible targeted therapy. Mutations in cell-cycle regulation and chromatin remodeling genes have been identified in chordomas, but their significance remains unknown. Investigation of the immune microenvironment of these tumors suggests that checkpoint protein expression may influence prognosis, and adjuvant immunotherapy may improve patient outcome. Finally, growing evidence supports aberrant growth factor signaling as potential pathogenic mechanisms in chordoma. In this review, we characterize the impact on treatment opportunities offered by the genomic and immunologic landscape of this tumor.